2021
DOI: 10.1016/j.ekir.2021.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Incidence, Recovery, and Long-term Kidney Outcomes Among Hospitalized Patients With COVID-19 and Influenza

Abstract: Introduction Acute kidney injury (AKI) is a common complication in patients with severe COVID-19. We sought to compare the AKI incidence and outcomes among patients hospitalized with COVID-19 and with influenza. Methods Retrospective cohort study of patients with COVID-19 hospitalized between March–May 2020 and historical controls hospitalized with influenza A or B between January 2017 and December 2019 within a large healthcare system. Cox proportional hazards models w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…The study demonstrated results comparable with ours, showing an association with specific comorbidities such as obesity and diabetes. 10 Furthermore, the histology assessment of the kidneys of H1N1-infected patients also demonstrated acute tubular necrosis (ATN), DIC, and myoglobin pigments, 11 showing that tubular necrosis may be the common mechanism of renal injury of patients infected with these respiratory illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated results comparable with ours, showing an association with specific comorbidities such as obesity and diabetes. 10 Furthermore, the histology assessment of the kidneys of H1N1-infected patients also demonstrated acute tubular necrosis (ATN), DIC, and myoglobin pigments, 11 showing that tubular necrosis may be the common mechanism of renal injury of patients infected with these respiratory illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Ng et al with CKD and non-CKD patients, 6.6% of the patients hospitalized due to COVID-19 developed AKI requiring dialysis, 17% of these patients survived, and 33.3% of the survivors, the kidneys did not improve at discharge [ 16 ]. In a study comparing COVID-19 with influenza, mortality and frequency of AKI were found to be higher in those with COVID-19, and 11% of patients with COVID-19 had a ≥ 25% GFR reduction from baseline at ≥ 90 days of follow-up [ 17 ]. In another study where patients who developed AKI due to COVID-19 were compared with patients who developed AKI due to another reason and upon follow-up after discharge, a greater decrease was observed in GFR of the COVID-19 patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension and cardiovascular diseases have generally been correlated with COVID-19, whereas they have been reported as the most common comorbidities along with diabetes mellitus [ 32 ]. Severe acute kidney injury and liver manifestations, even if they are not currently clearly elucidated, have long been reported [ 33 , 34 ].…”
Section: The Principles Of Diagnosing Covid-19mentioning
confidence: 99%